2004
DOI: 10.1177/1532673x04263801
|View full text |Cite
|
Sign up to set email alerts
|

Ideology and Learning in Policy Diffusion

Abstract: Scholarly research on the diffusion of policies across state governments focuses predominantly on the pathways of information between the states. Absent from this research is a thorough discussion of the content of the information state governments use when deciding whether or not to adopt an innovative policy. Given the importance of information in decision making, we develop a model that focuses attention on one type of information, namely, the ideological position of previous adopters. Although not the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
269
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(272 citation statements)
references
References 23 publications
(34 reference statements)
1
269
2
Order By: Relevance
“…EHA allows scholars to simultaneously account for both internal and external determinants of policy adoption. However, the policy-specific EHA approach emphasizes the unique determinants of specific policy instead of engaging in a broader discussion of government learning (Boehmke 2009;Grossback, Nicholson-Crotty, and Peterson 2004). A scholar looking at only a single policy may find a variable to be significant, but the same variable may not be a significant predictor of other policies relating to the same policy arena.…”
Section: Modeling Strategymentioning
confidence: 99%
“…EHA allows scholars to simultaneously account for both internal and external determinants of policy adoption. However, the policy-specific EHA approach emphasizes the unique determinants of specific policy instead of engaging in a broader discussion of government learning (Boehmke 2009;Grossback, Nicholson-Crotty, and Peterson 2004). A scholar looking at only a single policy may find a variable to be significant, but the same variable may not be a significant predictor of other policies relating to the same policy arena.…”
Section: Modeling Strategymentioning
confidence: 99%
“…For example, an important debate in this literature involves the use of contiguity or regional proximity as a proxy for peer groups. Scholars employing a monadic approach must define a peer group and then measure average ideological similarity (e.g., Grossback, Nicholson-Crotty, and Peterson 2004) Importantly, Volden's (2006) application of dyadic event history analysis to state Children's Health Insurance Program policy finds that internal state characteristics have little effect on program modifications whereas external characteristics of leader states, such as wealth, and relative characteristics, including similar government ideology, have statistically and substantively large effects on emulation. Appropriately, then, the dyadic event history approach brings the literature closer to Walker's (1969) original focus on policy leadership rather than merely policy adoption.…”
Section: Boehmkementioning
confidence: 99%
“…Other studies consider that policy entrepreneurs or successful peers are supportive for the diffusion process (Mintrom, 1997;Mintrom and Vergari, 1998). Evidence was found that controversial policies spread along ideological peers (Gray, 1973;Grossback et al, 2004). A newer wave of research increasingly tries to disentangle various mechanisms such as learning, competition or socialization, which drive the diffusion process (Dobbin et al, 2007;Gilardi et al, 2009;Meseguer, 2005;Shipan and Volden, 2008).…”
Section: Policy Diffusion In Federal Statesmentioning
confidence: 95%